GP102 Paediatric abdominal x-rays: appropriate or unnecessary requests?. (June 2019) - Ryan, Ciara; Tormey, Peter; Moylett, Edina
Abstract : Introduction: Paediatricians play a significant role in preventive healthcare 1 . There is a strong link between radiation exposure and the development of cancer 2 . The typical dose of radiation required for an abdominal x-ray (AXR) is 0.46 mSv, which is the equivalent approximate dose to 35 chest x-rays 3 . AXRs are frequently ordered for children in our hospital by staff in paediatric, surgical and Emergency Departments (ED) who may be unaware of the guidelines surrounding clinical indications for AXRs. Aims: To review the indications for paediatric AXRs requested in our hospital and compare them to the Royal Children's Hospital, Melbourne (RCHM) Guidelines 4, which are considered the gold standard. Methods: AXRs performed in University Hospital Galway from 1st June - 30th November 2018, on children ≤14 years old, were identified. Those ordered from the Neonatal Intensive Care Unit and those ordered directly by the patient's General Practitioner were excluded. Details including patient age, clinical indication, requesting specialty, existing diagnoses and previous presentations with the same complaint were collected from the online radiology system. Results: A total of 132 AXRs were identified, 83 of which were included in the analysis. In accordance with RCHM guidance, 49.4% (n=41) of requests were appropriate. Bowel obstruction and foreign body ingestion were the commonest indications for appropriate requests; constipation and non-specific abdominal pain were the commonest inappropriate requests. The paediatric department requested 55 AXRs, 49% (n=27) considered appropriate; the surgical department requested 9, zero considered appropriate. The ED requested 17 AXRs, 70.5% (n=12) considered appropriate. Conclusion: During the 6-month period, over half of the AXR requests were deemed inappropriate and may have been avoided. Further education concerning AXR indications should be directed at paediatric and surgical teams primarily to minimise unnecessary investigations and limit radiation exposure. References: Chang VY, Davidson TB ( 2015). Childhood Exposures and Risk of Malignancy in Adulthood. Pediatric Annals . 44(11), e270–e273. Willis CE, Slovis T L ( 2005). The ALARA concept in pediatric cr and dr: dose reduction in pediatric radiographic exams — a white paper conference. American Journal of Roentgenology, 184(2), 373–374. Linet M, Kim K, Rajaraman P ( 2008). Children's exposure to diagnostic medical radiation and cancer risk: epidemiologic and dosimetric considerations. Pediatric Radiology, [online] 39(S1), pp.4–26. Available at: https://link.springer.com/article/10.1007/s00247–008–Z1026–3. The Royal Children's Hospital Melbourne ( 2019). Clinical Practice Guidelines, Radiology - Acute Indications . [online] Available at: https://www.rch.org.au/clinicalguide/guideline_index/Radiology_Guidelines_Acute_indications/.